Switchable Solubility of Azobenzene‐Based Bolaamphiphiles. Issue 13 (7th June 2019) - Urner, Leonhard H.; Schade, Boris; Schulze, Maiko; Folmert, Kristin; Haag, Rainer; Pagel, Kevin
Abstract: The ability to design amphiphiles with predictable solubility properties is of everlasting interest in supramolecular chemistry. Relevant structural parameters include the hydrophobic–hydrophilic balance and structural flexibility. In this work, we investigate the water solubility of azobenzene‐based triglycerol bolaamphiphiles (TGBAs). In particular, we analyzed the structural effects of backbone hydrophobicity, flexibility, and cis/trans isomerization on the water solubility of a subset of five TGBAs. This leads to the first example of a non‐ionic bolaamphiphile whose water solubility can be changed by irradiation with light. The underlying kinetics were monitored using liquid chromatography and a closer analysis of the underlying aggregation processes provides a mechanistic understanding of the light‐driven dissolution process. We anticipate that the results obtained will help to engineer bolaamphiphiles with predictable solution properties in the future. Abstract : Switchable Solubility ! The ability to synthesize amphiphiles with tailored solution properties is of everlasting interest in supramolecular chemistry. Here, we present a set of azobenzene‐based bolaamphiphiles and show how water solubility can be tuned by synthetic modifications or by irradiation with light.